Pengaruh Upah Minimum Dan Pengeluaran Mikro Terhadap Pendapatan Daerah Di Indonesia - Agus Eko Sujianto; Ariza Rizki Rosidah; Refina Aulida Hijri; Siti Muhjatun Naziyah; Rifqi Nur Khusaini (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The minimum wage is very effective as a tool to reduce income inequality. Apart from limiting the minimum wage in general, this policy also has an effect on increasing income and plays an important role in overcoming income gaps. Apart from the minimum wage, micro-spending also influences income inequality. This research aims to determine and analyze the influence of minimum wages and micro expenditure on regional income in Indonesia. This research uses multiple linear regression analysis. The data used is secondary data for 1 period, namely 2022, obtained from the Central Statistics Agency. The variables used are Regional Income (Y), Minimum Wage (X1), Micro Expenditures (X2). The classic assumption test uses the SPSS for Windows version 25 program. The estimation results show that the provincial Minimum wages affect poverty in Indonesia, education affects poverty in Indonesia, and health affects poverty in Indonesia. Local minimum wages, education, and health influence poverty in Indonesia.